HAEMATOLOGICAL VALUES IN TUFTED CAPUCHIN (CEBUS APELLA) REARED IN CAPTIVITY - Ospina S., Pedro A. (2009)
The objective of the present study was to determine referential hematological values of the tufted capuchin (Cebus apella) maintained in captivity at the Patronato del Parque de Las Leyendas, Lima. A total of 32 primates (25 males and 7 females), among juveniles, sub adults and adults, in apparent good conditions were used. The primates were i.m. anesthetized with a combination of ketamine (10 mg/kg/bw) and xylazine (1 mg/kg/bw). The samples were obtained by puncture of the femoral vein using vacutainers with EDTA as anticoagulant. The red blood cell (RBC) and white blood cell (WBC) count were performed using the chamber of Neubauer, the platelet count and differential using the Wright stain, the hemoglobin (Hb) with the cianometahemoglobin method, the hematocrit (Ht) with the microhematocrit method and the eritrocitic indexes applying standard formulas with RBC, Hb and Ht values. The average values were RBC: 5.12 x 106/μl, WBC: 7.2 x 103/μl, neutrophils: 50.8%, lymphocytes: 47.6%, monocytes: 0.15%, eosinophils: 1.06%, basophils: 0.4%, platelets: 227 x 103/μl, Hb: 12.4 g/dl, Ht: 37.97%, VCM: 76.04 fl, HCM: 24.8 pg, CHCM: 32.6 g/dl. There were not significant differences due to age or sex.